2021
DOI: 10.1186/s13287-021-02583-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cell therapy in atopic dermatitis and chronic urticaria: immunological and clinical viewpoints

Abstract: Allergic diseases are immune-mediated diseases. Allergies share a common immunopathogenesis, with specific differences according to the specific disease. Mesenchymal stem/stromal cells (MSCs) have been applied to people suffering from allergic and many other diseases. In this review, the immunologic roles of MSCs are systemically reviewed according to disease immunopathogenesis from a clinical viewpoint. MSCs seem to be a promising therapeutic modality not only as symptomatic treatments but also as causative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 155 publications
(207 reference statements)
0
3
0
2
Order By: Relevance
“…Specifically, MSC therapy offers an attractive substitute for immune disorder treatments, including those of relapsing or refractory types ( 47 ). The effects of MSCs in AD are well reviewed by Kim et al ( 48 ); Th2 polarization shift, decrease in IgE levels, allergen-specific Tregs elevation, Th2 cytokine downregulation, and eosinophil level reduction. Similar to reported immunomodulatory MSC effects, we successfully demonstrated that cAT-MSCs reduced eosinophil, IgE, and PEG2 levels, and elevated the percentage of Tregs in an experimental canine DFE ointment-induced AD model.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MSC therapy offers an attractive substitute for immune disorder treatments, including those of relapsing or refractory types ( 47 ). The effects of MSCs in AD are well reviewed by Kim et al ( 48 ); Th2 polarization shift, decrease in IgE levels, allergen-specific Tregs elevation, Th2 cytokine downregulation, and eosinophil level reduction. Similar to reported immunomodulatory MSC effects, we successfully demonstrated that cAT-MSCs reduced eosinophil, IgE, and PEG2 levels, and elevated the percentage of Tregs in an experimental canine DFE ointment-induced AD model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the immunoregulatory and anti-inflammatory function [ 19 ], EVs from MSCs could be an alternative that can replace the current therapeutic protocol for AD [ 66 ]. Indeed, it was demonstrated that EVs from adipose-derived stem cells (ADSCs) could alleviate AD by reducing serum IgE, infiltration of inflammatory cells, and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Although this form of treatment looks promising, trials are new, and the chances of success are still low. But if it is successful, it may appear more frequently in the future as a radical and preventive treatment option [17].…”
Section: New Developments In Diagnosis and Therapy Of Allergic Diseasesmentioning
confidence: 99%